The Relationship Between Government Spending and Productivity in Iraqi Economy for The Period (2004-2022) - kadhim mohi, gawad; Mahdi Abbas Al-Birmani , Salah (Journal of Economics and Administrative Sciences, 2024)
The study examined the government expenditure patterns in Iraq, specifically focusing on its fundamental components: current and investment expenditure and total and partial productivity. The problem of the study arises in answering the following question: Does government spending have a role in increasing the productivity of the Iraqi economy? The study aims to determine whether government expenditure substantially influences the improvement of the Iraqi economy’s productivity. The objective was to thoroughly analyze the alterations in government expenditure over the research duration and assess the magnitude of any deviations. Furthermore, to assess the efficiency of public expenditure and examine various methods of gauging its productivity, investigating the correlation between government outlays and productivity. The study employed a descriptive-analytical approach to assess the fiscal expansion program in Iraq, particularly in the period following 2003. The main reason for this is allocating a substantial amount of government funds to non-productive current expenses, which has little effect on production. Furthermore, the public expenditure base index, which signifies the ideal proportion of government spending on GDP, varies from 25% to 35%. This metric represents the extent of government involvement in the economy. In Iraq, substantial government interference has been in economic activities, accompanied by a consistent rise in public expenditure rates. The primary cause of this is mainly attributed to the circumstances the country experienced post-2003, wherein the breakdown of infrastructure necessitated the provision of extensive services. Furthermore, the private sector is in its early stages and cannot stimulate development and foster economic expansion. Hence, governmental engagement in economic and social matters is imperative. Paper type: Research paper